Analisis Etika Lembaga Legislatif Perspektif Fiqih Dusturiyah - Syafdillah Sastri Syam; Nurfadillah Nurfadillah; Kurniati Kurniati (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Political ethics As a result, those who want a government that is fair and based on ethical values have a lot to learn from what happened. The goal is that they can create peace by upholding the values of justice. The research method used is the library method. If resistance is not based on proper moral and ethical principles, it will lead to uncertainty. Its power will inevitably collapse, especially if the leader does not instill moral values. Therefore, good rulers are those who create happiness rather than the opposite. The legislative body is in charge of making or drafting laws.